Spiritualitas Kepemimpinan Kaum Awam dalam Gereja Sinodal - Nerius Seto; Mutiara Andalas (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
In order for a Synodal Church to be realized, laypeople are essential. All members must actively participate in walking together, but especially the laity, who are crucial to the establishment of a synodal church. The challenge in aiming for a synodal church is the absence of lay participation. This is because of the laity's ignorance of their role in establishing a synodal church, their perception of the church as hierarchical, and their lack of comprehension of spirituality in ministry. According to Christophe Pierre (2021), "Synodality involves a spirituality of affirmation of the Spirit expressed in an attitude of understanding, discernment, and decision-making."  In the Synodal Church, lay leadership spirituality is very important. How does the encounter-based spirituality of laity leadership function within the Synodal Church? by employing a literature review and descriptive analysis with an emphasis on the spirituality of laity leadership. According to KTI, SG Art. 6:12, "synodality is the modus vivendi et operandi (mission and vocation) of the Church, which walks together." Finding the spirituality of laity leadership in the realization of a synodal church is the research's outcomeAbstrakKaum Awam berperan penting dalam mewujudkan Gereja Sinodal. Di mana berjalan bersama dengan melibatkan semua anggota untuk berperan aktif ambil bagian, terutama kaum awam yang memiliki peran penting dalam mewujudkan Gereja Sinodal. Kurangnya keterlibatan kaum awam menjadi permasalahan yang muncul dalam mengusahakan Gereja Sinodal. Hal ini karena kurangnya pemahaman awam mengenai keterlibatan mereka dalam mewujudkan Gereja Sinodal, karena pandangan mengenai Gereja masih hierarkis, serta kurangnya pemahaman mengenai spiritualitas dalam pelayanan. Chirstophe Pierre (2021) memaparkan bahwa: “sinodalitas melibatkan sebuah spiritualitas penegasan Roh yang diekspresikan dalam sikap memahami, menimbang-nimbang, dan memutuskan.” Spiritualitas kepemimpinan awam memiliki peranan penting dalam Gereja Sinodal. Bagaimana spiritualitas kepemimpinan awam melalui perjumpaan dalam Gereja sinodal? Dengan berfokus pada spiritualitas kepemimpinan awam, menggunakan pendekatan riset pustaka dengan analisis deskriptif. ‘Sinodalitas merupakan modus vivendi et operandi (misi dan panggilan) Gereja, yang berjalan bersama’ (KTI, SG Art. 6:12). Hasil dari penelitian ini adalah menemukan spiritualitas kepemimpinan awam dalam mewujudkan Gereja sinodal.